Physiological Motivational Meanings of Farmer's Chant 'Amang Kasuruan' During the Cap Tikus Production (Semiotic Analysis, Ethnolinguistic Approach) - Rambing, Christy C.; Warouw, Maya P.; Kaunang, Ivan R. B. (Edumaspul: Jurnal Pendidikan, 2023)
The cultural legacy holds a position of utmost richness in the collective human society. It manifests in diverse forms, with cultural traditions displaying unparalleled uniqueness across regions. These distinctive traits, deeply ingrained in the societal fabric, are exemplified by various customs, including the reverence for indigenous languages expressed through song. The significance of regional languages, especially in indigenous or cultural musical compositions, profoundly influences the everyday lives of communities. North Sulawesi, with its diverse tribes, epitomizes a cultural mosaic characterized by rich mores and customs. Among these, the South Minahasa tribe prominently utilizes the Tountemboan language as a linguistic emblem. This vernacular permeates daily discourse, not only in conversations but also resonating within the verses of songs and chants, inseparable from their artisanal endeavors. This study explores the motivational significance embedded in folk songs utilized during the intricate process of crafting Cap Tikus, a cultural artifact interwoven with the region's agricultural pursuits. The amalgamation of labor and lyrical expression in this context provides an intriguing subject for investigation, acting as a catalyst for instilling enthusiasm and fortitude among farmers, particularly those dedicated to cap tikus cultivation. Methodologically, the research employs a descriptive qualitative approach following Spradley's framework. It is supplemented by Semiotic analysis, drawing from Ferdinand Saussure's perspective on signs in the social milieu. Additionally, the study integrates Abraham Maslow's theory of motivational needs, outlining a hierarchical structure that encompasses physiological or basic needs. The explication of motivational underpinnings, ensuring the fulfillment of basic needs, unfolds through the impassioned rendition of folk songs during the cap tikus farming process. In essence, this research reveals the profound layers of motivation inherent in the ritualistic singing of folk songs, elucidating their role as markers and signifiers within the lyrical fabric. The comprehensive explication of these motivational meanings serves as a testament to the intricate interplay between cultural expressions, agricultural practices, and the fulfillment of fundamental human needs.